The Development of a Deep Learning-Based Chatbot for Stock Keeping Unit (SKU) Management - Hendra Julianto; Gautama Wijaya; Haeruddin Haeruddin (Universitas Ibn Khaldun Bogor, 2024)
Digital communications platforms, one of the revolutionary breakthroughs brought by rapid technological development. Such breakthroughs include technology in chatbots, which has now become a mighty tool, especially within the commercial sectors. This research hence focuses on the evolution of a chatbot in solving SKU management problems through deep learning technologies, such as the Multilayer Perceptron neural networks. The chatbot's goal is to deliver precise and effective information on SKU codes, stock levels, and product characteristics. The chatbot showed a high accuracy rate of 98% in answering questions about the given dataset after extensive testing. The findings demonstrate the potential of chatbots with deep learning to improve customer service and operational effectiveness in companies